Effect of epiphytic lactic acid bacteria isolated from guinea grass on nutritional value of the silages - Pasebani, Mahdi; Yaakub, Halimatun; Alimon, Abdul Razak; Sijam, Kamaruzaman (Academic Journals, 2011)
An investigation was carried out to isolate and identify predominant indigenous and epiphytic lactic acid bacteria from guinea grass. The effects of epiphytic lactic acid bacteria on the nutritional value and aerobic quality of the silages were also studied. The standard plate counts of naturally occurring bacteria in guinea grass were estimated to 2.65 × 105 CFU/g in fresh grass while the amount for epiphytic lactic acid bacteria were only 8.3 × 103 CFU/g. Isolations were carried out by 10 fold serial dilution which resulted in 18 purified bacteria. Three indigenous bacterial species comprised of Flavimonas oryzihabitans, Enerobacter cloacae, Sphingomonas paucimobilis B and four epiphytic lactic acid bacteria included of Weissella confusa, Weissella paramesenteroides, Leuconostoc mesenteroides ssp. dextranicum, and Lactococcus lactis ssp. hordniae were identified by BIOLOG identification system. The four lactic acid bacteria were individually applied in inoculation of guinea grass silage at the rate of 1 × 105 CFU/g in fresh grass. Fixed amount of MRS broth was considered as a carrier for inoculation of these lactic acid bacteria and thereby, two controls (with and without broth) were proposed to evaluate the effect of carrier separately. Six treatments of silages were opened on days 14, 21 and 28 in three replications. Temperature, pH value, proximate and van soest analysis and ammonia nitrogen were measured for each silage sample. Epiphytic lactic acid bacteria were effective to increase crude protein and crude fat while acid detergent fiber, neutral detergent fiber and ammonia nitrogen declined significantly. Decreasing of pH value was speeded up in all inoculated silages and hence, the silage reached to stable phase on day 14 and remained stable up to day 21 and 28. The inoculated silages were remained in the accepted range of pH value up to 48 h when they exposed to the air.